The Effectiveness Of Growing Media And Bio-Organic Fertiliser Application On The Growth And Yield Of Pak Choi (Brassica Rapa Var. Chinensis) For Sustainable Agriculture In Simalungun - Hiskia Simanjuntak; Desi Sri Pasca Sari Sembiring; Hanifah Mutia Zaida Ningrum Amrul (Jurnal Multidisiplin Dehasen (MUDE), 2026)
The study was conducted to determine the effectiveness of the growing medium and the application of organic fertilizer on the growth and production of bok choy. This study used a completely randomized design with two treatment factors. The first factor was the application of organic fertilizer, consisting of D0 (control), D1 (bioorganic dose of 20 g/plant), D2 (bioorganic dose of 30 g/plant), and D3 (bioorganic dose of 40 g/plant). The second factor was the use of growing media: M0 (soil), M1 (soil:husk 1:1), M2 (soil:husk 1:2), and M3 (soil:husk 2:1). The application of organic fertilizer significantly affected the height and weight of bok choy plants. The application of 40 g of bioorganic fertilizer (D3) showed the best results.